Объяснение:
1) либо (6x-3)=0
6x-3=0
6x=-3
x=0.5
либо (1+8x)=0
1+8x=0
8x=-1
x=-⅛
ответ: x = 0.5, x= - ⅛
2) ax+3x+4a+12= (ax+3x)+(4a+12)= x(a+3) + 4(a+3)= (x+4)(a+3)
X³+21+3x+7x²= (x³+7x²)+(21+3x)= x²(x+7) + 3 ( 7+x)= (x²+3)(x+7)
5y(y-2)-(2-y)= - 5y(2-y)-(2-y)= (-5y-1)(2-y)
Объяснение:
1) либо (6x-3)=0
6x-3=0
6x=-3
x=0.5
либо (1+8x)=0
1+8x=0
8x=-1
x=-⅛
ответ: x = 0.5, x= - ⅛
2) ax+3x+4a+12= (ax+3x)+(4a+12)= x(a+3) + 4(a+3)= (x+4)(a+3)
X³+21+3x+7x²= (x³+7x²)+(21+3x)= x²(x+7) + 3 ( 7+x)= (x²+3)(x+7)
5y(y-2)-(2-y)= - 5y(2-y)-(2-y)= (-5y-1)(2-y)